Adaptation of Regulatory Systems in Schoolchildren, Residing in Industrial Area - Aiman E. Konkabaeva (Evropejskij Issledovatelʹ, 2013)
The article presents the results of the study of heart rate variability (HRT) in apparently healthy volunteers of both sexes without bad habits, aged 16-18, residing in industrial region (Temirtau) and the ones, studying under innovative technologies. HRT was registered with the help of computer-controlled devices “Varikard” (Russia). The changes of HRT spectral indexes towards integral impact of vegetative regulation mechanisms and parasympathetic activity decrease and regulatory systems overexertion, demanding correction methods implementation